Towards a universal social protection model in Latin America - Filgueira, Fernando (ECLAC, 2014)
This document analyzes the State’s role in social matters, in terms of social insurance and protection, social promotion and investment, and its distributive and redistributive role. It also describes changes and major trends in the region’s social investment and protection between the beginning of the twentieth century and the 1980s and outlines what is being termed “the reform of social reforms” in the twenty-first century, in the light of the challenges of the region’s social development. Three recent models of universalism are presented, as well as the debates on their potential and limitations. The paper concludes with a summary of the universalist social protection project emerging in the region.